2020
DOI: 10.1186/s43066-020-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effects on tumor cells of the synthesized gold nanoparticles against Hep2 liver cancer cell line

Abstract: Background: Currently, nanomaterials (NMs) research and development is at a fastest pace due to the enhanced implication in different areas of applications. The synthesis of such NMs through biosynthesis methods is gaining much importance because of low cost involved and environment-friendly approach. In this present study, the nanoparticles (NPs) are synthesized using a medicinal plant, with anticancer properties so as to incorporate the therapeutic activity within the NPs, such that the NPs will have the att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 23 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…The formation of AuNPs was confirmed by the development of colour which is characteristic of AuNPs. The confirmation was done by recording the UV-Vis absorbance was at 350-650 nm which corroborated with the earlier published results [14,32] in which the UV-Vis spectral analysis of AuNP absorbance was measured at 520-560 nm (27). They confirmed the peak around 540 nm and a broader peak between 700 and 800 nm.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The formation of AuNPs was confirmed by the development of colour which is characteristic of AuNPs. The confirmation was done by recording the UV-Vis absorbance was at 350-650 nm which corroborated with the earlier published results [14,32] in which the UV-Vis spectral analysis of AuNP absorbance was measured at 520-560 nm (27). They confirmed the peak around 540 nm and a broader peak between 700 and 800 nm.…”
Section: Resultssupporting
confidence: 88%
“…Despite possessing significant advantages, use of AuNPs has its own limitation due to application of various hazardous chemical synthesis methods for preparation. Hence, green synthesis method using plants, microbes, seaweeds, and its respective bioactive metabolites is used to synthesize AuNPs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, they increase the longevity of vesicles in circulation (Borborema et al., 2016 ). It was reported that nanocarriers smaller than 500 nm can penetrate the bloodstream efficiently (Priya & Iyer, 2020 ). ZP is an important indicator of formulation stability as a higher surface charge produces repulsive forces that prevent particle coalescence and aggregation (Ahmed et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The optimization of the underlying parameters such as temperature and pH was carried out, which played crucial role in the synthesis (Kamala Priya and Iyer 2014b). The applications of gold nanoparticles (Kamala Priya and Iyer 2015b), in vitro cytotoxicity (Kamala Priya and Iyer 2019a) and anticancer assay (Kamala Priya and Iyer 2014c, 2019b, 2020a and anti-HIV assay (Priya et al 2021) were carried out in different cell lines. The results demonstrated non-toxicity of the nanomaterials to normal cell line.…”
Section: Preparation Of Nanoparticlesmentioning
confidence: 99%